International News : bulletin of the Provisional International. - Revolutionary Workers League (RWL) (Chicago : Demos Press, 1945)
In 1945 mede uitgegeven door 'Leninist League of Great Britain' en 'Central Comittee of the Red Front of Greater Germany'
Fonds Perrone
Engels
Periodiek
Keywords: communistische pers; Verenigde Staten